Prolonged duration of response in lenvatinib responders with thyroid cancer (Russian translation) - A. G. Gianoukakis; C. E. Dutcus; N. Batty; M. Guo; M. Baig (Опухоли головы и шеи)
We present an updated analysis of lenvatinib in radioiodine-refractory differentiated thyroid cancer (RR-DTC) with new duration of response (DOR) data unavailable for the primary analysis. In this randomized, double-blind, multicenter, placebo-controlled phase 3 study, patients ≥18 years old with measurable, pathologically confirmed RR-DTC with independent radiologic confirmation of disease progression within the previous 13 months were randomized 2:1 to oral lenvatinib 24 mg/day or placebo. The main outcome measures for this analysis are DOR and progression-free survival (PFS). The median DOR for all lenvatinib responders (patients with complete or partial responses; objective response rate: 60.2 %; 95 % confidence interval (CI) 54.2–66.1) was 30.0 months (95 % CI 18.4–36.7) and was generally similar across subgroups. DOR was shorter in patients with greater disease burden and with brain and liver metastases. Updated median PFS was longer in the overall lenvatinib group vs placebo (19.4 vs 3.7 months; hazard ratio (HR) 0.24; 99 % CI 0.17–0.35; nominal P <0.0001). In lenvatinib responders, median PFS was 33.1 months (95 % CI 27.8–44.6) vs 7.9 months (95 % CI 5.8–10.7) in nonresponders. The median DOR of 30.0 months seen with patients who achieved complete or partial responses with lenvatinib (60.2 %) demonstrates that lenvatinib responders can have prolonged, durable and clinically meaningful responses. Prolonged PFS (33.1 months) was also observed in these lenvatinib responders.